A Comparison of Students’ Perceptions Toward Listen-Read-Discuss and Contextual Redefinition Strategies in Learning Reading Comprehension (Aqualitative Study) - Lilih Insyirah; Munir; Murni Mahmud (International Journal of Language, Education, and Literature, 2025)
This study focuses on exploring students’ perceptions of the Listen-Read-Discuss (LRD) Strategy and Contextual Redefinition Strategy (CRS) in enhancing reading comprehension in an EFL setting. Conducted using a qualitative approach, the research involved high school students selected through simple random sampling. Interviews were used to collect data, and thematic analysis was employed to interpret students’ experiences with the two strategies. The findings revealed that students generally responded positively to both LRD and CRS. Students appreciated the structured flow of the LRD strategy — listening to information, reading the text, and participating in discussions — although some noted challenges in maintaining concentration during the listening stage, which occasionally disrupted their comprehension. Meanwhile, students perceived CRS as beneficial in enabling them to predict and understand word meanings through contextual clues, leading to a deeper grasp of the text. Overall, while both strategies were seen as helpful, students slightly favored the CRS approach for improving their reading comprehension. Keywords: Listen-Read-Discuss, Contextual Redefinition, Reading Strategies, EFL, Student Perceptions, Reading Comprehension, Comparison.